Human brain harbors single nucleotide somatic variations in functionally relevant genes possibly mediated by oxidative stress [version 3; referees: 2 approved] - Anchal Sharma; Asgar Hussain Ansari; Renu Kumari; Rajesh Pandey; Rakhshinda Rehman; Bharati Mehani; Binuja Varma; Bapu K. Desiraju; Ulaganathan Mabalirajan; Anurag Agrawal; Arijit Mukhopadhyay (F1000Research, 2017)
Somatic variation in DNA can cause cells to deviate from the preordained genomic path in both disease and healthy conditions. Here, using exome sequencing of paired tissue samples, we show that the normal human brain harbors somatic single base variations measuring up to 0.48% of the total variations. Interestingly, about 64% of these somatic variations in the brain are expected to lead to non-synonymous changes, and as much as 87% of these represent G:C>T:A transversion events. Further, the transversion events in the brain were mostly found in the frontal cortex, whereas the corpus callosum from the same individuals harbors the reference genotype. We found a significantly higher amount of 8-OHdG (oxidative stress marker) in the frontal cortex compared to the corpus callosum of the same subjects (p<0.01), correlating with the higher G:C>T:A transversions in the cortex. We found significant enrichment for axon guidance and related pathways for genes harbouring somatic variations. This could represent either a directed selection of genetic variations in these pathways or increased susceptibility of some loci towards oxidative stress. This study highlights that oxidative stress possibly influence single nucleotide somatic variations in normal human brain.